(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The problems of inefficient operation of sugar factories in Ukraine are considered. Attention is paid to optimizing the operation of the evaporation section of a sugar factory, which provides steam to all the main production units of the plant and determines the energy efficiency of the entire production. Problems in sugar production that reduce the competitiveness of the industry in Ukraine are identified. The conducted research has determined the influence of juice quality indicators on sugar quality and shortcomings in the evaporation process control system, which are associated with changes in the operation mode of the evaporation unit. It is shown that if the quality indicators of sugar raw materials are not taken into account, both the quality of products and the efficiency of the entire production management system are reduced. Problems in the functioning of the evaporation process optimization system are identified. Taking into account the complexity of the juice evaporation process in a multi-body evaporation plant and the influence of many process indicators, both technological and qualitative, the main vectors of the management process for optimizing juice evaporation by qualitative indicators are determined. The main criteria for the efficiency of sugar production, regulatory requirements, theoretical foundations and practical experience in implementing and using quality criteria in the optimization system in countries that use energy-efficient and competitive technologies in sugar production are considered. The effectiveness of the proposed product quality criteria for mathematical support of the evaporation process control system is substantiated.It was concluded that the obtained efficiency criterion for qualitative indicators makes it possible to use the proposed mathematical software for optimizing the operating modes in the juice evaporation control system in a multi-body evaporator of a sugar factory.